PREDICTION OF BUCKLING LOAD OF STEEL RACKING FRAME USING NON DESTRUCTIVE METHOD - Kalaikumar, V.; Kurian, V.J.; Narayanan, S.P; Shahir Liew, Mohd; Nabilah , A.B. (2010)
ABSTRACT In storage industries, steel racking frames are widely used to store the goods. Due to the limitation of the storage space, the capacities of the frames are stretched to the ultimate limit. In determining the load capacity of the steel racking frame, a non destructive method is required. A method for predicting the buckling load of steel racking frame using the measured natural frequency is proposed in this work. Simple experiments and numerical analysis were carried out and the results were compared with analytical values. The results confirmed the possibility of adopting the said method to determine the capacity of the steel racking frame.